Web-CAN interface for access control and monitoring - Ribeiro, Fernando Reinaldo (2011)
This paper describes a web-based system which allows the user to manage and to do real time monitoring the access to the educational building spaces, using two data nets. The first one is based on the CAN bus for data acquisition and actuation tasks to which are connected control devices like, magnetic cards readers, door locks and sensors. The second one is an Internet/Intranet infrastructure and uses standard web technologies like PHP and Java to provide an effective control and real time monitoring. This system is implemented on the Linux operating system using the Apache HTTP server and make use of standard technologies in use on the Web, to make an effective campus-wide security system. To close the gap between these two nets we used a CAN/Intranet gateway. In this paper the system layout and its main components are described.